2013
DOI: 10.1128/jvi.01008-13
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the Pseudomonas aeruginosa Myovirus ϕKZ Morphogenetic Protease gp175

Abstract: Pseudomonas aeruginosa myovirus KZ has a 270-kb genome within a T‫72؍‬ icosahedral capsid that contains a large, unusual, and structurally well-defined protein cylindrical inner body (IB) spanning its interior. Proteolysis forms a pivotal stage in KZ head and IB morphogenesis, with the protease gp175 cleaving at least 19 of 49 different head proteins, including the major capsid protein and five major structural IB proteins. Here we show that the purified mature form of gp175 is active and cleaves purified IB s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…The catalytic triad of T4 gp21 is formed by Ser 140 , His 85 and Asp 168 , consistent with earlier sequence analyses (Liu and Mushegian, 2004; Thomas and Black, 2013). Residues 140 and 85, which had been mutated to alanines (Figure 2), are located in β–strand 6, and in the loop connecting α-helix 1 to β–strand 4, respectively, whereas Asp 168 is situated in β–strand 8.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The catalytic triad of T4 gp21 is formed by Ser 140 , His 85 and Asp 168 , consistent with earlier sequence analyses (Liu and Mushegian, 2004; Thomas and Black, 2013). Residues 140 and 85, which had been mutated to alanines (Figure 2), are located in β–strand 6, and in the loop connecting α-helix 1 to β–strand 4, respectively, whereas Asp 168 is situated in β–strand 8.…”
Section: Resultssupporting
confidence: 89%
“…Sequence alignment of the T4 gp21 protease with proteases of other tailed phages and herpesviruses (Liu and Mushegian, 2004; Thomas and Black, 2013) predicted Ser 140 and His 85 to be the gp21 residues involved in catalysis. To avoid possible self-cleavage, we produced a gp21 mutant which had alanines in positions 140 and 85.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this precedent, we hypothesized that the scaffold protein of a giant phage might also be cleaved. Since we had previously demonstrated that the KZ prohead protease gp175 is active in vitro and its cleavage specificity is known (11,35), we sought to determine whether gp54 was a substrate for gp175. The gp54 gene was cloned with the codons for an N-terminal His 6 tag.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the core of the bacteriophage T4 prohead contains, in addition to ~580 copies of the scaffolding protein, 7 extra proteins with copy numbers ranging from 40 to 370. 13,22 Procapsids of many phages (like T4, HK97, φKZ, and λ) contain head maturation proteases (serine proteases in case of T4 13,22 and φKZ 23 ) which are activated after prohead assembly and degrade the internal core partially or completely. The digestion products exit the prohead, freeing the space for the genomic DNA.…”
Section: Capsid Assemblymentioning
confidence: 99%
“…148 Despite the low sequence similarity, these proteins have similar structures, indicating that the sheath proteins of tailed phages have evolved from a common ancestor. In the DSY3957 crystal structure the N-terminal arm (residues [15][16][17][18][19][20][21][22][23][24][25] of the protein is a part of a β-sheet in the C-terminal domain of a symmetry related molecule. Based on this observation, Leiman and Shneider 128 proposed that in the phage sheaths such chain swapping cross-links neighboring subunits stacked on top of each other, thus helping to maintain the sheath integrity.…”
Section: Structure Of the Phage Tailsmentioning
confidence: 99%